POTENSI JENIS LEBAH MADU KELULUT (Trigona spp) UNTUK MENINGKATKAN EKONOMI MASYARAKAT DESA GALANG KECAMATAN SUNGAI PINYUH KABUPATEN MEMPAWAH - Lukman, Lukman; Hardiansyah, Gusti; Siahaan, Sarma (Universitas Tanjungpura, 2020)
The Trigona bee is a small black insect with a body length of 3-4 mm and a wingspan of 8 mm. East Kalimantan has found Trigona spp bees, namely T. laeviseps, T. apicalis, T. Drescheri. T. fucibasis, T. fuscobalteata, T. insica, T. itama, T. melina and T. terminate. This study aims to determine the potential of kelulut honey bees (Trigona spp) in the community honey farmer group of Galang Sungai Pinyuh Village, Mempawah Regency, to identify the types of kelulut bees (Trigona spp) in the box (stup) thatÂ made by the honey farmer group of Galang Village. Sungai Pinyu, Mempawah Regency, Analyzing the additional economic income of the Galang Village community, Sungai Pinyuh District, Mempawah Regency. This research was conducted in Galang Sungai Pinyuh Village Mempawah Regency which was conducted for 1 month in the field, by using the survey method, by using the method, which is the activity of finding the existence of a species that is the object of bee research. There are 2 types of Trigona spp bees cultivated in the Galang Kelulut Honey Forest Farmers Group, namely H. itama Cockerel, and H. bakeri, and processing of kelulut honey (Trigona spp) will benefit greatly from the services of kelulut honey (Trigona spp). Harvesting of kelulut honey from honey farmers is 15-30 liters / month. The selling price for consumers is around IDR 400,000 for every 1 liter. From the research above, it is concluded that the potential of kelulut honey bees (Trigona spp) can increase the income of the people of Galang Village, Sungai Pinyuh District, Mempawah Regency.Keywords: Community economy, Potency, Trigona.